Constituent Order in Old Icelandic - Longo, Michele (Folia Scandinavica Posnaniensia, 2025)
The prevailing perspective in scholarly literature is that Old Icelandic exhibits free word order in terms of sentence constituent linearity. However, when examining head-complement order, the consensus is that Old Icelandic represents an OV language transitioning towards VO, as seen in modern Icelandic. This paper aims to elucidate the fundamental order of Old Icelandic by classifying languages based on the position of constituents (S, V, O) within sentences. The investigation begins with the question of what statistical insights can be gleaned from IcePaHC, an annotated corpus documenting the entire history of the Icelandic language from its earliest written records (1150) to contemporary times (2008). In this study, data were analyzed using the HistobankVis System, which allows for the extraction of percentages across various time periods. The findings suggest that Old Icelandic should be characterized by two predominant orders (SVO and VSO) rather than as a free-order language.